Estrategias de marketing educativo para incrementar la demanda del servicio educativo en la Institución Educativa N° 80521 de Santiago de Chuco - 2 014 - Rodriguez Montoro, Cesar Enrique (2019)
ABSTRACT The purpose of this research work was to determine educational marketing strategies aimed at increasing the demand for educational services in the Educational Institution No. 80521 of the city of Santiago de Chuco. The descriptive propositive design was used, as well as the analytical synthetic and statistical method, with a sample consisting of 173 parents. The survey, documentary analysis, and descriptive statistics such as frequency distribution, figures, were applied as a data collection technique. Through the results obtained, it can be seen that in the Educational Institution under study, the trend of the average growth rate of students enrolled in the primary level is negative in (2.45)%, while for the secondary level it only grows in 0.17% for the period 2009 2014. The causes of the decrease in the demand for the educational service are due in the first place to the lack of academic demand according to 26% followed by the competence of the educational institutions according to 18%, poor practice of values according to 12% of parents of family, not giving importance to economic and family problems, so it is inferred that the father of the family is willing to sacrifice himself for giving a good education to his children. Likewise, 42% of the parents declare to be dissatisfied with respect to the quality of service provided by the Educational Institution. In order to increase the demand of the educational service, strategies of marketing mix, retention and loyalty of students for the Educational Institution N ° 80521 were developed.